Development of a genetic algorithm for the design of cellular manufacturing systems from a new function of fitness (2007)
This article shows a genetic algorithm that makes possible to fnd a feasible and acceptable solution to a manufacturing cell formation problem. The proposed genetic algorithm includes a new approach of the usually known aptitude function for this kind of problem resulting in a more exact solution. In order to validate the algorithm genetic operators this work includes a practical example with an imaginary company which wants to organize four manufacturing cells taking in account 30 different products using 10 machine types.